Characteristics of antrochoanal polyps in the pediatric age group - Al-Mazrou, Khalid A. (Medknow Publications, 2009)
OBJECTIVES: To evaluate and compare the clinical and the pathological characteristics of antrochoanal polyps (ACPS) in adults and children. MATERIALS AND METHODS: Medical records of 35 patients (19 children, 16 adults) operated upon for ACPS between 1995 and 2005 at an academic tertiary center were reviewed retrospectively. Demographic characteristics, clinical presentation, surgical management, histological findings and recurrence rate were compared. RESULTS: Of the 35 patients, 19 (54%) were children (mean age, 12.6 years) and 16 (46%) were adults (mean age, 31.4 years). Nasal obstruction was the most common presenting symptom in both groups. The incidence of snoring and/or obstructive sleep apnea was statistically significant, more common among the pediatric age group as compared to the adult group (P =.001). Epistaxis was also found to be more common among the pediatric age group (P =.027), while sinusitis was noted to be significantly more common among the adult group (P =.019). Transnasal endoscopic removal of ACPS was performed in 12 (63.1%) children and 11 (68.7%) adults. A combined open/endoscopic approach was required in 36.9% of children and 31.3% of adults. On histologic examination, allergic ACPS (the mucosal surface is respiratory epithelium, no mucus glands, abundant eosinophils) was more common than inflammatory ACPS (the mucosal surface is respiratory epithelium, no mucus glands, abundant neutrophils) in children (2.8:1) as compared to adults (0.8:1) (P =.045). All of our patients were followed with endoscopic examination for a period ranging from 9 to 42 months (mean, 24 months). Recurrence of ACPS was identified in 2 children and 1 adult. CONCLUSION: Antrochoanal polyps are a rare clinical entity. Children have unique clinical and pathological features as compared to adults. Endoscopic excision is safe and effective in the pediatric age group and has the capability to ensure complete removal and lower recurrence rate.